A novel GCaMP6f-RCS rat model for studying electrical stimulation in the degenerated retina - Azrad Leibovitch, Tamar; Farah, Nairouz; Markus, Amos; Mandel, Yossi (Frontiers in Cell and Developmental Biology, 2024)
Background: Retinal prostheses aim to restore vision by electrically stimulating the remaining viable retinal cells in Retinal Degeneration (RD) cases. Research in this field necessitates a comprehensive analysis of retinal ganglion cells’ (RGCs) responses to assess the obtained visual acuity and quality. Here we present a novel animal model which facilitates the optical recording of RGCs activity in an RD rat. This model can significantly enhance the functional evaluation of vision restoration treatments. Methods: The development of the novel rat model is based on crossbreeding a retinal degenerated Royal College of Surgeons (RCS) rat with a transgenic line expressing the genetic calcium indicator GCaMP6f in the RGCs. Characterization of the model was achieved using Optical Coherence Tomography (OCT) imaging, histology, and electroretinography (ERG) at the ages of 4, 8, and 12 weeks. Additionally, optical recordings of RGCs function in response to ex-vivo subretinal electrical stimulations were performed. Results: Histological investigations confirmed the high expression of GCaMP6f in the RGCs and minimal expression in the inner nuclear layer (INL). OCT imaging and histological studies revealed the expected gradual retinal degeneration, as evident by the decrease in retinal thickness with age and the formation of subretinal debris. This degeneration was further confirmed by ERG recordings, which demonstrated a significant decrease in the b-wave amplitude throughout the degeneration process, culminating in its absence at 12 weeks in the GCaMP6f-RCS rat. Importantly, the feasibility of investigating subretinal stimulation was demonstrated, revealing a consistent increase in activation threshold throughout degeneration. Furthermore, an increase in the diameter of the activated area with increasing currents was observed. The spatial spread of the activation area in the GCaMP6f-RCS rat was found to be smaller and exhibited faster activation dynamics compared with the GCaMP6f-LE strain. Conclusion: This novel animal model offers an opportunity to deepen our understanding of prosthetically induced retinal responses, potentially leading to significant advancements in prosthetic interventions in visual impairments.